CURRENT ISSUES OF ORAL REHABILITATION IN DENTO-MAXILLO FACIAL ASYMMETRY - Madalina Matei; Mihaela Cezarina Mehedinți; Popa Gabriel Valeriu; Stefănescu Ada; Kamel Earar (Romanian Society of Oral Rehabilitation, 2020)
The issue of reciprocal influences between anxiety and dento-maxillo-facial rehabilitation in children is complex. The child patient is primarily afraid of pain. Between child and adult there is not only a difference in size but also an essential one in terms of morpho-functional features of his body. The child who frequently comes for dental care is the child between 6-14 years old and with a much lower incidence than the one between 3-6 years old. Material and method: The study included 25 patients, between January 1, 2019 and January 1, 2020, aged between 11 and 20 years, with dento-maxillary anomalies, without a history of orthodontic treatments. Results and discussions:The deviation of the interincisive lines at the jaw and mandible, is the essential manifestation of the asymmetries and, together with the difference in amplitude of the sagittal gap of the molars, is the sign of symmetry; the gap of the interincisive points in maximum intercuspidation does not allow us to determine the type of symmetry. Conclusions:Addressing the asymmetries from a clinical point of view is more difficult than other anomalies, being necessary for the clinical examination to group all the symptoms that allow the formulation of an accurate diagnosis